Mitochondrial Dysfunction as Substrate for Arrhythmogenic Cardiomyopathy: A Search for New Disease Mechanisms - van Opbergen, Chantal J. M.; den Braven, Lyanne; Delmar, Mario; van Veen, Toon A. B. (Frontiers in Physiology, 2019)
Arrhythmogenic cardiomyopathy (ACM) is a familial heart disease, associated with ventricular arrhythmias, fibrofatty replacement of the myocardial mass and an increased risk of sudden cardiac death (SCD). Malignant ventricular arrhythmias and SCD largely occur in the pre-clinical phase of the disease, before overt structural changes occur. To prevent or interfere with ACM disease progression, more insight in mechanisms related to electrical instability are needed. Currently, numerous studies are focused on the link between cardiac arrhythmias and metabolic disease. In line with that, a potential role of mitochondrial dysfunction in ACM pathology is unclear and mitochondrial biology in the ACM heart remains understudied. In this review, we explore mitochondrial dysfunction in relation to arrhythmogenesis, and postulate a link to typical hallmarks of ACM. Mitochondrial dysfunction depletes adenosine triphosphate (ATP) production and increases levels of reactive oxygen species (ROS) in the heart. Both metabolic changes affect cardiac ion channel gating, electrical conduction, intracellular calcium handling and fibrosis formation; all well-known aspects of ACM pathophysiology. ATP-mediated structural remodeling, apoptosis and mitochondria-related alterations have already been shown in models of PKP2 dysfunction. Yet, the limited amount of experimental evidence in ACM models makes it difficult to determine whether mitochondrial dysfunction indeed precedes and/or accompanies ACM pathogenesis. Nevertheless, current experimental ACM models can be very useful in unravelling ACM-related mitochondrial biology and in testing potential therapeutic interventions.